The Role of The Head of Madrasah in Ensuring The Quality of Education at Islamic Educational Institution - Tomi; Mila Mutiara Qoirunisa; Mukhlisatinnisa Amalia; Subiyantoro (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2025)
Educational quality is a key element in creating excellent and competitive educational institutions, including madrasahs. Madrasah principals play a strategic role in designing quality policies, conducting supervision, and ensuring the continuity of quality educational processes. This study aims to analyze the role of madrasah principals in controlling and supervising educational quality at MTs Darul Ulum Islamic School Sleman, a pesantren-based madrasah that was newly established in 2021 but has shown significant development. This study uses a descriptive qualitative approach with data collection techniques through participatory observation, semi-structured interviews, and document analysis. Informants were selected purposively, consisting of the madrasah principal, teachers, administrative staff, and foundation administrators. The results of the study indicate that the madrasah principal plays a role in setting quality standards, conducting periodic evaluations, and mentoring teachers through participatory supervision. However, there are still challenges in quality documentation, limitations in follow-up on evaluation results, and uneven leadership distribution. This study contributes to the development of a madrasah leadership model that integrates Islamic values, modern quality management principles, and sustainable institutional systems within the context of Islamic education.